FUNCTIONS PREFERENCES OF HANDBOOKS' TECHNOLOGY & INFORMATICS EDUCATION OF ELEMENTARY SCHOOL TEACHERS - WALAT, Wojciech (Trends in education, 2009)
In article was by Q typology - checked what was the preferences of teachers of elementary schools they are in range of detailed functions of textbooks to teaching of technology & informatics - is different from his theoretical model somewhat. Teachers prefer training (practical) function clearly, and further self-teaching and motivational functions. They show less paradoxically on informative and educational function. Distinguished features of studied teachers' group on preferences of textbook features it had not influence such as: the age, size the locality in which is the school, nor the kind of finished studies. It miscarried also to show the groups of features of textbooks preferred by teachers particularly.
Keywords: handbooks; function of handbooks; verification of handbooks.